Chasing intermediate hosts of Echinococcus multilocularis at the southern edge of its European distribution using red fox stomach content analysis - Cafiero Salvatore Andrea; Cenni Lucia; Rossi Chiara; Pascoe Emily Louise; Obber Federica; Da Rold Graziana; Citterio Carlo Vittorio; Casulli Adriano; Hauffe Heidi Christine; Massolo Alessandro (International Journal for Parasitology: Parasites and Wildlife)
Echinococcus multilocularis (Em) is a Taeniidae cestode circulating among canids (definitive hosts) and among voles (intermediate hosts). Humans can develop alveolar echinococcosis (AE) following egg ingestion. In Italy, Em is present in red foxes (Vulpes vulpes) from the Trentino-Alto Adige/Südtirol Region, with reports in canids from Liguria (wolf, Canis lupus, and domestic dog, Canis lupus familiaris) and Tuscany (wolf and red fox) Regions. The first autochthonous case of human AE was recently confirmed in the Province of Bolzano. Despite its relevance, the intermediate hosts maintaining the Em life cycle in this area have never been identified.This study aimed to fill this knowledge gap by collecting ingested rodents from the stomachs of 148 legally culled or found dead foxes across the Province of Bolzano. For 142 prey items, species was ascertained from tissue DNA using a PCR of a 350 bp fragment of cytb mitochondrial gene. Positivity to Em was investigated by RT-PCR and conventional PCR on organ tissues from 97 rodents targeting a 69 bp fragment of cob and a 126 bp fragment of nad2 mitochondrial genes, respectively.Microtus arvalis was the most common prey rodent in terms of both frequency in foxes (20.8 %; 30/144) and total rodent prey items (81.7 %; 116/142). Other prey species included nine Arvicola amphibius, five Microtus lavernedii, two M. subterraneus, one M. liechtensteini, six Clethrionomys glareolus, one Apodemus flavicollis and two Ap. sylvaticus. Only 3/97 rodents were Em-positive (M. arvalis; 3/85) in two Em-positive red foxes. Prevalence in M. arvalis was estimated at 0.035 (95 % CI: 0.008–0.103). Further research is required to explain why Em distribution is limited to this area in the eastern Italian Alps despite the spatial contiguity to hyperendemic foci.